Delineation of recharge areas of the aquifer systems of Corinthia prefecture by the use of isotopic evidence - Antonakos, A.; Nikas, K. (Bulletin of the Geological Society of Greece, 2013)
The results of a ground water isotopic research program conducted during the period 2004-2008 by an IGME/Hydrogeology Department team in the area of North Korinthian prefecture are presented here. 69 ground water samples were collected during the period 6/2007 and analyzed in the laboratory of Isotope Hydrology of NCSR "Demokritos" for Oxygen isotopes δ18O and Tritium. From the spatial distribution of δ18O, the conglomerate aquifer systems seem to be recharging from their outcrop areas and possibly laterally from the karstic systems that outcrops in higher altitudes. The rest aquifer systems of the area seem to be recharging exclusively from their outcrop areas with the exception of the Vocha coastal alluvial aquifer which seem to be recharging almost totally from waters coming from higher altitudes. According to the spatial distribution of Tritium in both Sikion–Velo and Vrachati– Lechaio areas, low Tritium values are observed which are indicative of the fact that the aquifer system of those areas are recharged from vertical seepage from the riverbeds of Asopos and Rachiani rivers respectively. Contrariwise in the area of Krines–Zevgolatio the high values of Tritium reveal the lateral recharge from the adjacent marine terraces and marl aquifers